Zion and Pentecost: The Spirituality and Experience of Pentecostal and Zionist/ Apostolic Churches in South Africa - Anderson, Allan H. (University of South Africa Press, 2000)
This publication is a cross-disciplinary study of African Pentecostalism in a South African urban environment. It provides an overview of the context, significance and growth of African Pentecostal and Zionist churches in South Africa, and compares the worship and liturgy of different Pentecostal and Zionist churches. Patterns of recruitment and growth are examined, as well as the role of preaching and hermeneutics in these churches. The author also examines the interaction between African Pentecostalism and traditional religious beliefs and practices, including the spirit world, the ancestors, traditional divination and healing, and burial rites. The author concludes with the challenges these African forms of Christianity pose to the whole church in its message and mission.